-3x + 18 = 7x
3x + (-3x) + 18= 7x + 3x
18 = 10x
18 10x
— = —
10 10
1.8 = x
Answer:
1/3⁵⁶ is the answer i think if it's not then i am sorry
Answer:
you do not have to state explicitly which limit law(s) you are using. 1 - 5n ... Q: 9) n(x) = 2x - 2 g(x)= x2 + 5 Find h(g(1) A) 5 B) 10 C) 21 D) 40.
Step-by-step explanation:
Answer:
Step-by-step explanation:
I haven't got time to do all these by I'll give you the method in each case.
You have to make the x or y term equal (or 1 term + and other -) in both equations before adding or subtracting.
A . Multiply equation 2 by 2 and subtract (to eliminate x)
- don't forget to multiply EACH TERM by 2.
B. Multiply equation 2 by -2 and add.
C. Multiply equation 1 by 3 and equation 2 by 2 ( this will give -6y and +6y in the resulting equations ) so you then add to eliminate y.
D. Multiply equation 1 by 13 and equation and equation 2 by 2 to eliminate x then add.
Answer:
I think the number of terms are 3